Unlocking Suburban Commons: Exploring Strategies for Reducing Vulnerability in a Socially Exposed Urban Area - Hall, Anders (My University, 2020)
In the Gothenburg suburb of Norra Biskopsgården, there is an urgent need for the community and municipality to end a downward spiral of socio-economic resignation and neighbourhood related stigma. In the bottom lies a long term ethnical, geographical, and economical segregation, today resulting in gaps in education level, possibility to find work and eventually economic freedom compared to the average in Gothenburg. By identifying the gaps in social and economic status, as well as the current usage of buildings and land in the area, this thesis aims to present a proposal for decreasing the social vulnerability. By removing physical barriers and using spaces to support socio-economic and cultural development, the goal is to connect the area to its surrounding neighbourhoods, support education, create a place for meaningful spare time and eventually decrease the opportunity for unwanted parallel societal structures to grow. On a strategic level this means working with how the public transport is utilized, adaptable densification and how to fight the No-Go zones. On the detailed level, it means to show how a community centre can be established in the border zone between Norra Biskopsgården and Länsmansgården. The community centre aims to serve youth activities after school, as well as provide facilities to support the circular economy with workshops suitable for arts and craft, and second-hand refurbishing. This thesis can serve as a platform for short and long-term interventions in the area, also a starting point for dialogue among the local stakeholders, residents, housing companies, city district representatives, local Non-Governmental Organisations (NGO´s) and business owners.